Mass transfer enhancement in spacer-filled membrane channels by flow oscillation induced vortex shedding: Numerical study of the effect of amplitude. (1st August 2023) - García-Picazo, F.J.; Fletcher, D.F.; Fimbres-Weihs, G.A.
Highlights: Oscillating flow amplitude-mass transfer relationship studied comprehensively. Dependence of mass transfer on the strength and location of vortices is analysed. Oscillating flow amplitude affects the location of vortex shedding onset. Mass transfer improves as the amplitude increases, until a maximum is reached. Cost-effective amplitude is proposed in terms of mass transfer and power number. Abstract: Techniques inducing unsteady flow have shown potential for promoting vortex shedding in membrane channels, affecting the boundary layer and increasing mass transfer. This work reports a CFD study of the effect of the characteristics of an oscillating flow (i.e., frequency and amplitude) on the occurrence of vortex shedding. The implications of imposing an oscillating flow are analysed by comparing mass transfer enhancement and required pumping power. Results show that the resonant frequency for the perpendicular velocity component does not maximise mass transfer, but it yields a significant increase. For Re = 300, a normalised amplitude of 0.01 appears as a balanced trade-off between mass transfer and pressure drop. The location of onset of vortex shedding in the channel moves upstream as the amplitude increases. Mass transfer reaches an upper limit as the amplitude increases, when the onset of vortex shedding reaches the first filament. The phenomena taking place in a 2D spacer-filled membrane channel, and their implications for real-world applications, are discussed. Graphical abstract: Image, graphical abstract